Mechanical evaluation of six techniques for stable fixation of the sagittal split osteotomy after counterclockwise mandibular advancement - De Oliveira, Leandro Benetti [UNESP]; Reis, Jose Mauricio Nunes [UNESP]; Spin-Neto, Rubens; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Oguz, Yener; Pereira-Filho, Valfrido Antonio [UNESP] (Elsevier, 2016)
We have evaluated the resistance to displacement of six stable methods of fixation of a sagittal split ramus osteotomy (SSRO) in the mandibular advancement with counterclockwise rotation. We tested 60 synthetic hemimandibles in six groups of 10 each: Group I - fixation with a straight four-hole 2.0 mm miniplate; Group II - a straight six-hole 2.0 mm miniplate; Group III - two straight 2.0 mm four-hole miniplates; Group IV - an eight-hole 2.0 mm (grid plate); Group V - a 2.0 mm four-hole straight miniplate and 2.0 × 12 mm bicortical screw; and Group VI - a straight four-hole 2.0 mm locking miniplate. We applied a linear force in the region between the canine and the first premolar using a universal testing machine (EMIC- DL2000) with a loading cell of 10 KN. The loads at 1, 3, and 5 mm displacement were recorded (N) and the data transmitted from the load cell to a computer. Results were analysed using analysis of variance (ANOVA) (p < 0.001) and the Tukey post-test for comparison of the significance of the differences between the groups. For the three degrees of displacement, fixation with two straight 2.0 mm plates and with the grid plate gave higher load values.
Keywords: Bone plate; Rigid internal fixation; Sagittal split ramus osteotomy